Credit Union Names. (June 2015) - Chen, Lindsey N.H.
<x content-type="archive" xml:space="preserve">Abstract</x> This study examines 301 California credit union names in an effort to uncover naming patterns. These names provide key markers for the field of membership that not only identify the prospective members of the credit union, but also emphasize the sense of community that underlies credit unions (as opposed to stockholder-based financial institutions). Collectively, the credit union names highlight the geographic, ethnic, economic, and social diversity that characterizes California. The results of this study may contribute to knowledge of business naming practices.